The curious history of God - Stannard, Russell; Davies, Taffy (Philadelphia, Pa. : Templeton Foundation Press, 2003)
Explores different ways in which the Bible portrays God and shows how people's understanding of God has changed and developed over the course of history.
Originally published: Oxford, England : Lion Pub., 1999.
Keywords: God -- Juvenile literature; God